Relationship between the Subscales of Mental Health and Spiritual Health in Staff of Kermanshah University of Medical Sciences in 2016 - Arash Ziapour; Arsalan Ghaderi; Hosna Vafapoor; Vahid Yazdani; Shahram Saeidi; Alireza Zangeneh (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: Spiritual health is a valuable asset that affects humans' mental health. The purpose of this study was to investigate the relationship between the mental health and spiritual health among the staff of Kermanshah University of Medical Sciences in 2016. Method: In this cross-sectional study, 267 employees of Kermanshah University of Medical Sciences were surveyed by simple random sampling. The data collection tools included Goldenberg's General Health Questionnaire and Paloutzian and Ellison's Spiritual Well-Being Questionnaire. The collected data were analyzed using Pearson product moment correlation. In this research, all ethical issues were observed. In addition, the authors did not report any conflict of interests. Results: According to the results of the study, the mean mental health score was 2.98, while the mean score of spiritual health was 3.62. In addition, there was a significant correlation between the mental and spiritual health (r=0.324). Considering the subscales of mental health, spiritual health registered the highest and lowest correlations with depression and physical symptoms respectively. Conclusion: Improving the mental health of the effective and constructive population of the society is necessary for the dynamism, prosperity and promotion of the society. Spiritual health affects the university staff's mental health. Therefore, planning to promote it is an important issue that should be considered by the relevant authorities and policy makers. For downloading the full-text of this article please click here.